2013
DOI: 10.1111/syen.12049
|View full text |Cite
|
Sign up to set email alerts
|

Counting the spots: a molecular and morphological phylogeny of the spotted darner Boyeria (Odonata: Anisoptera: Aeshnidae) with an emphasis on European taxa

Abstract: Boyeria irene and Boyeria cretensis are species of spotted dragonflies belonging to the ‘darner’ family, Aeshnidae. In 1991, Peters classified Boyeria from Crete as B. cretensis, based on adult morphological characters. In this study, we used molecular evidence to determine if indeed B. irene and B. cretensis are different species. DNA was sequenced from samples of B. irene (from France, Switzerland, Tunisia, Spain and Italy) and B. cretensis (from Crete). These species were recovered as two different clades w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Some authors have differentiated between genera and species of odonates by combining morphological data and molecular analyses (Torres-Pachón et al, 2017;Baskinger et al, 2008;Hovmöller & Johansson, 2003). In B. irene Kohli et al (2014) found that the populations present in NW Spain (Galicia) could be genetically differentiated from those of the rest of the Iberian Peninsula but these researchers did not compare biometric data. If the three measures that we propose in this work are valid for the population of Galicia, it is something that requires further research.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have differentiated between genera and species of odonates by combining morphological data and molecular analyses (Torres-Pachón et al, 2017;Baskinger et al, 2008;Hovmöller & Johansson, 2003). In B. irene Kohli et al (2014) found that the populations present in NW Spain (Galicia) could be genetically differentiated from those of the rest of the Iberian Peninsula but these researchers did not compare biometric data. If the three measures that we propose in this work are valid for the population of Galicia, it is something that requires further research.…”
Section: Discussionmentioning
confidence: 99%
“…Similar study was carried out by Bybee et al (2008) and Carle et al (2015) have conducted the Phylogenetic studies of Anisoptera and recorded the evolutionary relationship of Anax and Aeshna as supported values (MLB=78%, BPP=99%) and (BP =20, PP=27) respectively. Similarly, Saux et al (2003) conducted phylogenetic study of Aeshnidae while, Kohli et al (2014) conducted study on genus Boyeria using morphological and molecular markers. Whereas many previous workers studied the molecular characterizations of odonata including members of Aeshnidae i.e., (Misof et al 2000;Artiss et al 2001;Misof et al 2001;Hesgawa et al 2006;Ware et al 2008;Elizabeth et al 2011;Kim et al 2014;Bybee et al 2016;Das 2016;Suvorov 2018;Kalavanti and Jethva 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, many workers done study on ribosomal gene, 16S rRNA and evaluated the comparison among phylogenetic relationship based on single and combined data sets of CO1 and 16S (Kambhampati and Charlton 1999). Many other workers have studied the molecular characterizations of various odonata species i.e., (Misof et al 2000;Artiss et al 2001;Misof et al 2001;Saux et al 2003;Hasegawa and Kasuya 2006;Ware et al 2007aWare et al , b, 2008Bybee et al 2008;Fleck et al 2008;Dumont et al 2010;Davis et al 2011;Elizabeth et al 2011;Kohli et al 2014;Kim et al 2014;Carle et al 2015;Bybee et al 2016;Das 2016;Suvorov 2018;Kalavanti and Jethva 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular analysis and phylogenetic reconstruction DNA extraction and sequencing DNA was extracted from one leg of each adult dragonfly using a GeneJet Genomic DNA Purification kit (Thermo Scientific, Waltham, USA). Three genes were amplified: mitochondrial cytochrome oxidase I (COI); hypervariable D7 region of the large-subunit 28S (rDNA) (28S); and nuclear Histone 3 (H3), using PCR according to Kohli's et al (2014) protocol. We selected two mitochondrial and one nuclear gene based on their diverse evolutionary rates, to allow us to reconstruct both internal and external branches, respectively (Fritz et al, 1994).…”
Section: Methodsmentioning
confidence: 99%